Data from: Temporal trends in body condition of arctic geese wintering in the Mississippi Alluvial Valley ... - Carlson, Lindsay Gray; Massey, Ethan; Osborne, Douglas (Dryad, 2019)
Midcontinent populations of arctic nesting geese (hereafter, arctic geese), including greater white-fronted geese Anser albifrons frontalis, lesser snow geese Anser caerulescens caerulescens, and Ross’s geese Anser rossii have increased in abundance and shifted their winter distribution in recent decades. Consequently, the number of arctic geese wintering in the Mississippi Alluvial Valley (MAV) has increased since the 1980’s. Stored endogenous nutrients are critically important to the life cycle of arctic geese as they are used to complete long-distance migration events, survive harsh winters, and supplement nutrients needed for reproduction. This study tracked temporal changes in body condition of arctic geese during the wintering period. Arctic geese were collected from October–February 2015–2016 and 2016–2017 in eastern Arkansas, USA. Proximate analysis was used to determine size of lipid and protein stores as an index of body condition. Protein stores were more stable through time than lipids, but a ...